2018
DOI: 10.1039/c8tc02484g
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-induced colloids towards robust fluorescent photonic crystal films and high performance WLEDs

Abstract: We fabricated dendrimer-modified colloids and utilized them to fabricate PC films with good mechanical strength and high performance WLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…To further modify the tiny cracks of P( t ‐BA) film, we utilize the G2 PAMAM dendrimer to graft onto the P( t ‐BA‐ co ‐MMA). As shown in Figure b, the P( t ‐BA‐ co ‐MMA)‐G2 PAMAM exhibits new absorption peaks at 1648 cm −1 and 1554 cm −1 , corresponding to C=O stretching (amide I) and C−N stretching (amide II) vibrations of the G2 PAMAM . Figure c,d shows the optical photographs and IR spectra of P( t ‐BA‐ co ‐MMA) and P( t ‐BA‐ co ‐MMA)‐G2 PAMAM PCs films, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further modify the tiny cracks of P( t ‐BA) film, we utilize the G2 PAMAM dendrimer to graft onto the P( t ‐BA‐ co ‐MMA). As shown in Figure b, the P( t ‐BA‐ co ‐MMA)‐G2 PAMAM exhibits new absorption peaks at 1648 cm −1 and 1554 cm −1 , corresponding to C=O stretching (amide I) and C−N stretching (amide II) vibrations of the G2 PAMAM . Figure c,d shows the optical photographs and IR spectra of P( t ‐BA‐ co ‐MMA) and P( t ‐BA‐ co ‐MMA)‐G2 PAMAM PCs films, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Those greatly restrict the PL enhanced efficiency of PC film in energy saving devices. To solve it, the polyamidoamine (PAMAM) dendrimer grafted onto the surface of P(St‐MMA‐AA) PCs could achieve crack‐free PCs film, which profited from the hydrogen bond interactions of dendrimer loaded P(St‐MMA‐AA) particles . Moreover, Jiang and co‐workers reported that the crack‐free PC films were carried out by using hydrophobic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In the above mentioned experiments, we found that the color of amPEN solution in DMF gradually changed to purple during the addition of Fe 3+ solution, which is different from other samples whose color variation is either derived from added metal ions (Co 2+ , Cr 3+ , Zr 4+ ) or possible oxidation of Fe 2+ . It is reported that the color of colloids solution is highly dependent on their morphology [43], thus we assumed that somewhat well-organized microstructures would be formulated following the coordination between Fe 3+ and synthesized amPEN. Therefore, we have verified the morphology evolution of Fe 3+ crosslinked amPEN at different experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…WLEDs with CIE coordinates of (0.3228, 0.3150), (0.3346, 0.3349), and (0.3491, 0.3562), and a color temperature between 6035 and 4865 K were successfully constructed using this material as the light conversion layer. [ 31 ] Rachod et al reported a rare‐earth white light‐emitting nanocomposite based on (CdSe) x (ZnS) 1− x /(CuInS 2 ) x (ZnS) 1− x QDs and silicone polymer, and made a systematic study on its optical properties and stability. [ 32 ] Xinsheng et al prepared light conversion films with high PLQY and used them in 405 nm near‐UV excited WLED devices by encapsulating blue, green, and red CdSe x S 1− x /ZnS QDs in ZIF‐8 MOFs.…”
Section: Recent Progress On Qd Materials For Wledsmentioning
confidence: 99%